2014
DOI: 10.1186/s12970-014-0058-3
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of a hydroethanolic extract from Bowdichia virgilioides on muscular damage and oxidative stress caused by strenuous resistance training in rats

Abstract: BackgroundNatural antioxidants can reduce oxidative damage caused by high-intensity resistance training (RT). We investigated the in vitro antioxidant potential of hydroethanolic extract (HEE) from Bowdichia virgilioides on muscular damage and oxidative stress in rats subjected to high-intensity RT.MethodsThirty-two male Wistar rats were divided into four experimental groups: 1) control group (CG), oral administration (P.O.) of vehicle; 2) trained group (TG), vehicle-treated with RT; 3) B. virgilioides untrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 62 publications
5
24
0
2
Order By: Relevance
“…Interestingly, terpenoids and alkaloids were not observed. Consistent with our findings, previous chemical investigation of B. virgilioides has revealed the presence of phenolic compounds (Arriaga et al, 2000;Dos Santos et al, 2014). Nowadays, phenolic compounds are well known because of their anti-inflammatory properties (Chan et al, 2013;Lu et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, terpenoids and alkaloids were not observed. Consistent with our findings, previous chemical investigation of B. virgilioides has revealed the presence of phenolic compounds (Arriaga et al, 2000;Dos Santos et al, 2014). Nowadays, phenolic compounds are well known because of their anti-inflammatory properties (Chan et al, 2013;Lu et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…In Brazil, the bark is used in folk medicine to treat different symptoms of inflammatory diseases (Brandao et al, 1992). Previous studies have reported that the extracts from B. virgilioides possess anti-inflammatory (Thomazzi et al, 2010), antinociceptive , and antioxidant (Dos Santos et al, 2014). However, the anti-allergic inflammatory effect of B. virgilioides has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In RE training, ROS/RNS are produced through diverse mechanisms, such as the xanthine and NADP(H) oxidase system, ischemia-reperfusion, prostanoid metabolism and also phagocytic respiratory bursts (Bloomer et al 2005;Goldfarb et al 2005). Although ROS/RNS stimulate important exercise-induced adaptions of the antioxidant and repair systems (Merry et al 2015), data suggests that an accumulation of intense or exhaustive periods of RE (most common in athletes of weightlifting and body builders) can promote an overproduction of ROS/RNS and provoke an increase in oxidative stress (Tanskanen, et al 2010;Kreher and Schwartz 2012;Dos Santos et al 2014). In humans, RE with submaximal intensity caused an excess of physical and oxidative stress, as well as post-exercise immunosuppression (Cakir-Atabek et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A Tabela 2 mostra os valores absolutos, potência pico, potência media, potência mínima, índice de fadiga 1 e índice de fadiga 2 dos corredores, obtidos pelo teste anaeróbio máximo. Por fim, no intuito de verificar associações entre as variáveis estudadas, realizou-se uma matriz correlacional, apresentada na Tabela A aptidão anaeróbia é um fator determinante de performance em provas desportivas em que é requerida a manutenção prolongada de grande potência e capacidade anaeróbia para o fornecimento de energia 2 , sendo um componente essencial para o bom desempenho em algumas modalidades esportivas, pois em determinados momentos, há a exigência de um esforço anaeróbio máximo [21][22][23] .…”
Section: Resultsunclassified